2013
DOI: 10.1111/liv.12311
|View full text |Cite
|
Sign up to set email alerts
|

Serum liver enzymes are associated with all‐cause mortality in an elderly population

Abstract: All serum liver enzymes were positively associated with long-term mortality in this elderly population. Why participants with low ALT and AST levels have higher risk of mortality remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 36 publications
12
81
2
2
Order By: Relevance
“…To propose possible factors contributing to the association between lower ALT and mortality is challenging given that, similar to our findings (Table 2), increasing ALT has been directly linked to components of the metabolic syndrome and to markers of insulin resistance and systemic inflammation [1,3,6,9]. The most widely accepted theory in current literature behind the association, is that low ALT is correlated with both frailty and sarcopenia, each associated with mortality in their own right [6,7].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…To propose possible factors contributing to the association between lower ALT and mortality is challenging given that, similar to our findings (Table 2), increasing ALT has been directly linked to components of the metabolic syndrome and to markers of insulin resistance and systemic inflammation [1,3,6,9]. The most widely accepted theory in current literature behind the association, is that low ALT is correlated with both frailty and sarcopenia, each associated with mortality in their own right [6,7].…”
Section: Discussionsupporting
confidence: 67%
“…The finding of a positive association between GGT and mortality would be consistent with its known function as a sensitive but non-specific marker of liver injury, alcohol intake, oxidative stress, vascular disease and other co-morbidities, through primary pathology and also through enzyme induction from medications [1,2,4,[9][10][11]48]. Indeed, this fact is supported by our finding that GGT >70 U/L associated with mortality in all three categories (cardiovascular, cancer and non-cardiovascular/non-cancer; Table 3).…”
Section: Accepted M Manuscriptsupporting
confidence: 63%
See 2 more Smart Citations
“…The authors concluded that in subjects with increased GGT levels, ultrasound examination of liver should be performed for diagnostic and risk stratification reasons (30). Other studies have demonstrated an association of GGT with mortality in elderly subjects (31,32).…”
Section: Ggt Cvd and Mortalitymentioning
confidence: 99%